Pengaruh Self Efficacy, Locus of Control, dan Lingkungan Kerja terhadap Kinerja Karyawan Warehouse (Studi Kasus di PT Cipta Krida Bahari Surabaya) - Alvio Mita Widya (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
This study aims to statistically prove the effect of Self Efficacy, Locus Of Control, and Work Environment on Warehouse Employee Performance. The sample method used in this study using this study is Non probability using Saturated Samples. The sample in this study was all employees of PT Cipta Krida Bahari Surabaya Warehouse totaling 84 respondents. The primary data obtained were analyzed by multiple regression analysis test through the SPSS 26 program. The results of this study show that partially Self Efficacy, Locus Of Control, and Work Environment have a significant effect on the performance of PT Cipta Krida Bahari Warehouse employees. Then simultaneously Self Efficacy, Locus Of Control, and Work Environment have a significant effect on the performance of PT Cipta Krida Bahari Warehouse employees.